IT-enabled strategic management : increasing returns for the organization - Walters, Bruce A., 1961-; Tang, Zaiyong, 1957-; Thomson Gale (firma) (Hershey, Pa. : Idea Group Publishing, 2006)
"This book makes an effort to explore the interaction of information technology and strategic management and aims to encourage joint research efforts among IT and strategy scholars for common solutions"--Provided by publisher.
Obsahuje bibliografii a rejstřík
Elektronická reprodukce.
Keywords: informační technologie; strategický management; information technology; strategic planning; kolektivní monografie; elektronické knihy; e-knihy online; collective monographs; electronic books; e-books online